1986
DOI: 10.1254/jjp.40.481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of the Tremorgenic Mycotoxin Fumitremorgin A

Abstract: Abstract-Some

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…When injected intravenously in experimental animals, FTA causes tremor and generalized tonic-clonic convulsion (2,3). The autonomic nervous system is also severely affected by this toxin (4), and all these effects may result from abnormal ex citation of the central nervous system (CNS).…”
mentioning
confidence: 99%
“…When injected intravenously in experimental animals, FTA causes tremor and generalized tonic-clonic convulsion (2,3). The autonomic nervous system is also severely affected by this toxin (4), and all these effects may result from abnormal ex citation of the central nervous system (CNS).…”
mentioning
confidence: 99%
“…In previous studies, the main site of con vulsant action of FTA has been suggested to be in some restricted areas in the brain stem, from the mesencephalon to the medulla oblongata (3,4). In the present study, the role of the brain stem in the convulsant effect of FTA was investigated in anesthetized rabbits.…”
Section: Discussionmentioning
confidence: 83%
“…Only a few indirect findings are available at present. Our previous study has shown that the FTA induced EEG arousal response is quite dif ferent from the typical seizure pattern caused by pentylenetetrazol (3). Therefore the me chanism of action of FTA may be different from that of pentylenetetrazol, although this drug is assumed to increase neuronal ex citability through its direct action on the cell membrane (8), and the most important site of its action is also considered to be in the me sencephalon (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations